Teacher’s Perceptions of Students’ Speaking Anxiety Problem at SMKN 4 Barru - Nurshafika; Muhammad Tahir; Amra Ariyani (International Journal of Language, Education, and Literature, 2026)
This study aims to explore teachers’ perceptions of students’ speaking anxiety problems at SMKN 4 Barru and the strategies used to address them. A descriptive qualitative research design was employed in this study. The data were collected through interviews with English teachers and analyzed thematically. The findings reveal that students’ speaking anxiety is caused by several factors, including lack of confidence, limited knowledge of speaking topics, fear of negative judgment from peers, and lack of experience in speaking in public. The teacher addresses these problems through three main stages: reception, understanding, and evaluation. In the reception stage, the teacher applies a supportive approach by motivating students and starting speaking activities with simple and familiar topics. In the understanding stage, the teacher identifies psychological and social factors that contribute to students’ anxiety. In the evaluation stage, relaxation techniques such as slow breathing and focusing strategies are used to help students manage anxiety and maintain classroom interaction. The study concludes that teachers’ awareness of students’ emotional conditions and the use of appropriate strategies play an important role in reducing students’ speaking anxiety and encouraging active participation in English speaking activities. Keyword: Teacher’s perception, Speaking, Anxiety Problem